Diamagnetic Shift of a InGaP-AlInGaP Semiconductor Single Quantum Well under Pulsed-magnetic Fields - 최병구; 김영민; 송진동 (한국진공학회, 2015)
Application of magnetic fields is important to characterize the carrier dynamics in semiconductor quantum structures. We performed photoluminescence (PL) measurements from an InGaP-AlInGaP single quantum well under pulsed magnetic fields to 50 T. The zero field interband PL transition energy matches well with the self-consistent Poisson-Schr？dinger equation. We attempted to analyze the dimensionality of the quantum well by using the diamagnetic shift of the magnetoexciton. The real quantum well has finite thickness that causes the quasi-two-dimensional behavior of the exciton diamagnetic shift. The PL intensity diminishes with increasing magnetic field because of the exciton motion in the presence of magnetic field.